2007
DOI: 10.1897/07-339
|View full text |Cite
|
Sign up to set email alerts
|

Species Sensitivity Distributions for Suspended Clays, Sediment Burial and Grain Size Change in the Marine Environment

Abstract: Assessment of the environmental risk of discharges, containing both chemicals and suspended solids (e.g., drilling discharges to the marine environment), requires an evaluation of the effects of both toxic and nontoxic pollutants. To date, a structured evaluation scheme that can be used for prognostic risk assessments for nontoxic stress is lacking. In the present study we challenge this lack of information by the development of marine species sensitivity distributions (SSDs) for three nontoxic stressors: susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 18 publications
2
29
0
1
Order By: Relevance
“…In another study performed by Oosterhout and Lürling (2011), Phoslock s induced toxic effects on a Daphnia galeata population, although these researchers stated that these toxic effects could be due to several factors acting in synergy. Other researchers studied the species sensitivity distribution of 12 species and four taxonomic groups exposed to bentonite, concluding that the organisms living in sediments are accommodated to address these clays at high density (Smit et al, 2008). Strachan and Kingston (2012) observed that different species of bivalves (Modiolus modiolus, Venerupis senegalensis, Dosinia exoleta, and Chlamys varia) increased their normal filtration rate when bentonite was added to the aqueous media.…”
Section: Animal Exposurementioning
confidence: 99%
“…In another study performed by Oosterhout and Lürling (2011), Phoslock s induced toxic effects on a Daphnia galeata population, although these researchers stated that these toxic effects could be due to several factors acting in synergy. Other researchers studied the species sensitivity distribution of 12 species and four taxonomic groups exposed to bentonite, concluding that the organisms living in sediments are accommodated to address these clays at high density (Smit et al, 2008). Strachan and Kingston (2012) observed that different species of bivalves (Modiolus modiolus, Venerupis senegalensis, Dosinia exoleta, and Chlamys varia) increased their normal filtration rate when bentonite was added to the aqueous media.…”
Section: Animal Exposurementioning
confidence: 99%
“…Barium, as barite, in drill muds is basically toxicologically inert (Neff, 2008;Smit et al, 2008). Suspended solids (e.g., barite, bentonite and cuttings particles) at high concentrations in the water column near the sediment-water interface can irritate gills and have other physical effects on benthic invertebrates (Barlow and Kingston 2001;Armsworthy et al, 2005;Smit et al, 2008). At the suspended solids levels (usually less than 5 mg/L) observed at Terra Nova (Suncor, 2011), any effects should be restricted to plankton and filter-feeding bivalves (Smit et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Suspended solids (e.g., barite, bentonite and cuttings particles) at high concentrations in the water column near the sediment-water interface can irritate gills and have other physical effects on benthic invertebrates (Barlow and Kingston 2001;Armsworthy et al, 2005;Smit et al, 2008). At the suspended solids levels (usually less than 5 mg/L) observed at Terra Nova (Suncor, 2011), any effects should be restricted to plankton and filter-feeding bivalves (Smit et al, 2008). However, abundances of Telliniade (Macoma), the dominant bivalve at Terra Nova, increased rather than decreased near drill centres and at higher sediment barium concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations